Analysis of preparation in the independent curriculum implementation: Case study on IPAS learning - Lia Wanti; Ika Chastanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The independent curriculum is a newly created implementation, so schools and teachers as educators play an important role in the success of the program. The purpose of this study is to analyze the preparation for the implementation of the independent curriculum and find out the preparation in the application of science learning which is a combination of science and social studies. The research was carried out from August 2022-January 2023, where the research was carried out at UPTD SD Negeri 09 Panai Tengah, Labuhanbatu Regency. The samples in this study were vice principals, curriculum representatives and grade 4 teachers as research subjects. Data collection techniques are carried out by in-depth interviews. This study used the miles and huberman method. The results of this study show that, in preparing for the implementation of the independent curriculum, there is science learning, schools will prepare learning equipment plans and prepare teaching materials, but still require training and application gradually. Currently, preparations towards the implementation of the independent curriculum in these schools have reached 75% and will be optimized and implemented in the 2023/2024 school year.Abstrak Kurikulum merdeka merupakan implementasi yang baru diciptakan, maka sekolah dan guru sebagai pendidik sangat berperan penting dalam menyukseskan program tersebut. Tujuan penelitian ini untuk menganalisis persiapan penerapan kurikulum merdeka serta mengetahui persiapan dalam penerapan pembelajaran IPAS yang merupakan kombinasi dari IPA dan IPS. Penelitian dilaksanakan mulai bulan Agustus 2022 – Januari 2023, tempat penelitian dilakukan di UPTD SD Negeri 09 Panai Tengah, Kabupaten Labuhanbatu. Sampel dalam Penelitian ini adalah wakil kepala sekolah, wakil bidang kurikulum dan guru kelas 4 sebagai subjek penelitian. Teknik pengumpulan data dilakukan dengan wawancara mendalam (In-depth Interview). Penelitian ini menggunakan metode miles dan huberman. Hasil penelitian ini menunjukkan bahwa dalam mempersiapkan penerapan kurikulum merdeka, ada pembelajaran IPAS, sekolah akan menyusun rencana perangkat pembelajaran dan mempersiapkan bahan ajar, namun masih membutuhkan pelatihan dan penerapan secara bertahap. Saat ini, persiapan menuju penerapan kurikulum merdeka di sekolah tersebut sudah mencapai 75% dan akan dioptimalkan serta diterapkan pada tahun ajaran 2023/2024.